The effect of customer perceived value on the repurchase decision in the clothing stores - Ashqui Cuvi, Ginger; Bermúdez Gallegos, Christian (Revista Universidad de Guayaquil, 2019)
Perceived value is a concept of growing interest among academics and Marketing professionalssince it generatessustainable competitive advantage due to its direct relationship with customersatisfaction and loyalty and is considered a reliable predictor of consumer buy-back readiness. The literature demands greater attention to this variable in developing countries. The authors summarize five components such as quality, price, hedonism, ethics, and health. The purpose of this study is to evaluate the components of perceived value that influence the customer’s repurchase decision in commercial clothing stores. These were validated through a quantitative approach with a nonexperimental design, with a descriptive scope of the perceived value and correlation with the repurchase decision. The resultsshow that the five components are statistically significant and that a higher perceived value of the customer, a greater decision to repurchase.